Literature Review: Plyometric Training in Volleyball - Impact on Power, Vertical Jump, and Athlete Performance - Qusyaeri, Ahmad Tamamudin; Amalia, Eneng Fitri; Rochman, Taupik (Universitas Suryakancana, 2025)
Plyometric training has become an integral component of modern volleyball training programs to improve explosive power and vertical jump performance. This literature review analyzed 45 empirical studies published between 2015-2024 to evaluate the effectiveness of plyometric training in volleyball athletes. The results of the analysis showed that plyometric training significantly increased vertical jump height (8-25%), explosive power (12-30%), and spike performance (10-20%) in volleyball athletes. Plyometric programs with a duration of 6-12 weeks, a frequency of 2-3 times per week, show optimal results. However, variations in training protocols, subject characteristics, and research methodologies create a heterogeneity of outcomes that need to be considered in practical implementation. This literature review provides evidence-based recommendations for practitioners in designing effective plyometric training programs for volleyball athletes.